BODY IMAGES: SHAPES OF THE FEMALE BODY IN CRISTINA GARCIA´S THE AGÜERO SISTERS - Fernández Sánchez, Paloma (2015)
The female characters in The Agüero Sister´s novel live the strict constrains imposed on female bodies. They are used, abused and modified to conform a pre-stablished body image leaving women with little to no agency. When these women swerve from the roles, attitudes and activities set up for them, they are both physically punished and socially excluded. All in all, Garcia´s novel evidences how the hegemonic discourse reduces the female body to a monolithic, a historic entity by the hegemonic discourse and uses it as a site to be controlled.